Society and politics in colonial Trinidad - Millette, James (Omega Bookshops CurepeTT, 1985)
Records history of Trinidad between 1783-1810. Discusses the Crown Colony System of Government with its regime of institutionalized dependance. Focuses on slavery, racism, the plantation system and the applicability of the `Westminister Model' to the West Indies. Examines the historical factors originally involved in the creation and development of a modern West Indian State.